Highlights on the Application of Genomics and Bioinformatics in the Fight Against Infectious Diseases: Challenges and Opportunities in Africa - Bah, Saikou Y.; Morang’a, Collins Misita; Kengne-Ouafo, Jonas A.; Amenga–Etego, Lucas; Awandare, Gordon A. (Frontiers in Genetics, 2018)
Genomics and bioinformatics is increasingly contributing to our understanding of infectious diseases caused by bacterial pathogens such as Mycobacterium tuberculosis and parasites such as Plasmodium falciparum. This ranges from investigation of disease outbreaks and pathogenesis, host and pathogen genomic variation, host immune evasion mechanisms and identification of potential diagnostic markers and vaccine targets. High throughput genomics data generated from pathogens and animal models can be combined with host genomics and patients’ health records to advice on treatment options, and potential drug and vaccine interactions. However, despite accounting for the highest burden of infectious diseases, Africa has the lowest research output on infectious disease genomics. Here we review the latest contributions of genomics and bioinformatics to the management of infectious diseases of serious public health concern in Africa, including tuberculosis (TB), dengue fever, malaria and filariasis. Furthermore, we discuss how genomics and bioinformatics can be applied to identify drug and vaccine targets. We conclude by identifying challenges of genomics research in Africa, highlighting how these can be overcome where possible.